New Polymeric Membrane Electrode for Clarithromycin Determination - Al-Saidi, Khaleda H; Munshid, Hayder Q (Al-Nahrain Journal of Science, 2018)
New polymeric membrane electrodes has been developed for the determination of Clarithromycin. The electrodes were constructed by incorporating the Clarithromycin-tetraphenylborate ion pair complex into a polyvinylchloride matrix plasticized by four plasticizers, Di-octyl phthalate (DOP); Di-butyl phosphate (DBP); Acetophenone (AP); Di-butyl phthalate (DBPH). These electrodes give sub- Nernstian slopes (51.206, 53.930, 58.104 and 58.484 mV/decade) and linear ranges from (1×10-5-1×10-3, 1×10-5-1×10-3, 5×10-5-1×10-3 and 1×10-5 -1×10-3 M) respectively. The best electrode was based on DBPH plasticizer which gave a slope 58.484 mV/decade, correlation coefficient 0.9961, detection limit of 9×10-6 M, lifetime 20 day and displayed good stability and reproducibility and used to determine the Clarithromycin in pharmaceutical samples. The interferences measurements were studied using the separated method for selectivity coefficient determination. The pH and life time of the electrodes were also studied.